PENGEMBANGAN KOMPETENSI PROFESIONAL GURU MELALUI PEMBELAJARAN DIFERENSIASI DI SEKOLAH DASAR - Endah Fidiarti; Lilis Kholisoh Nuryani; Sumiati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of teachers' professional competencies is the basic capital in the learning process of students to meet the learning needs of different students in a class. This type of research is a literature review (literature review), with stages namely collecting relevant research literature, marking several important terms in the research, conducting an in-depth analysis of the literature that has been obtained by compiling discussions, drawing conclusions based on the results of the analysis. The conclusion of this study is differentiated learning, especially in elementary school education units in developing learning that can meet the learning needs of students without exception. The essential aspects of the development process consist of planning, implementation, and evaluation. The role of the principal in the development of teachers' professional competencies through differentiated learning is by implementing programs that encourage the implementation of independent learning in schools, supporting educators to be open so that they enjoy learning, encouraging students' readiness in learning, thinking critically, and actively involving related parties to play a role in supervising students' learning achievement and encouraging cooperation between related parties to improve the qualifications of educators in the context of implementing the development of differentiated learning.